015 Can we predict liver fibrosis preoperative in patients who undergo heart failure surgery and does it influence postoperative liver function?. (16th May 2012) - Farre, N; Tilling, L; Rice, A; Simon, A; Banner, N R
Abstract : Background: Liver dysfunction is common in patients with heart failure and may progress to irreversible fibrosis, which is predictive of poor prognosis. Our objective was to determine the frequency of liver fibrosis in patients who died after heart failure surgery (Insertion of ventricular assist device (VAD) or heart transplantation) and to identify predictors of liver fibrosis. Methods: We identified 19 patients who died after a median of 24 days after heart failure surgery. Liver sections were analysed post-mortem for the presence of fibrosis which was staged according to the scheme: 0=none, 1=portal or limited perivenular/perisinusoidal, 2=portal, perivenular and sinusoidal, 3=bridging fibrosis and 4=cirrhosis. Clinically relevant fibrosis was defined as stage 3 or 4. Pre- and post-operative data were analysed to identify predictors of fibrosis. Results: Mean age was 45±11 years. 14/19 patients were male. 84% had non-ischaemic cardiomyopathy, 8 patients received a heart transplantation and 11 patients a VAD, 21% of patients had previous heart failure surgery (VAD or transplantation). Eight patients had stage 3 or 4 fibrosis (42%, 2 patients had cirrhosis and 6 bridging fibrosis, group F+), 11 had 0–2 stage (group F−). F+ patients had higher pre-operative right atrial pressure (16±9 vs 11±4 mm Hg, p=0.18) and a higher incidence of moderate to severe tricuspid regurgitation (75% vs 25%, p=0.07), but cardiac index was similar (median 1.7 (IQR 1.4–2.15) in F+ vs 1.8 (1.4–2.8) in F−, p=0.60). There were no differences in biochemical measurements of renal or liver function: creatinine 97 μmol/l (88–226) in group F+ vs 104 (81–113) in F−, bilirubin in F+ 30 (22–43) μmol/l vs 22 (12–53) in F−, alanine transaminase 27 μmol/l (16–231) vs 33 (18–107); and alkaline phosphatase 78 μmol/l (69–101) vs 90 (70–144). A higher international normalised ratio (INR) was seen in F+ (2.4±0.6 vs 1.6±0.5, p=0.013), but F+ had a greater warfarin exposure than F− (62% vs 9%, p=0.067). To correct for the higher incidence of warfarin therapy in F+ we analysed the Model for End Stage Liver Disease-IX (MELD-IX) score. This was higher in group F+ (19.4 (14.4–25.6) vs 15.2 (9.4–21.6), p=0.13). Patients in F+ had a higher post-surgery need of blood products than F−: red blood cell units 38 (15–42) vs 17 (2–35), p=0.18; plasma units 11 (6–27) vs 7 (1–20), p=0.43; and platelets units 9 (5–13) vs 2 (1–15), p=0.71. F+ patients had a higher bilirubin than F− at day 8 post-surgery (127 μmol/l (48–218) vs 20 (17–56), p=0.032). Conclusion: Liver fibrosis was common in patients who did not survive heart failure surgery, but could not be predicted from preoperative clinical and biochemical markers, although there was a trend to be associated with more severe tricuspid regurgitation. Fibrosis was associated with more postoperative liver dysfunction. *FN and TL authors contributed equally to the work.